Pengaruh dan keseimbangan Teknologi Digital dalam dunia Pendidikan - Hafid, Nasya (Maliki Interdisciplinary Journal, 2025)
The development of digital technology has brought major changes to the world of education. The changes that have occurred have been felt and are truly real. These changes have several influences on the world of education. On the one hand, digital technology has offered various opportunities to improve the quality of learning, such as increasing educational accessibility and facilitating more interactive learning. However, on the other hand, inappropriate use of technology can cause problems such as gadget addiction and lack of social interaction. This article discusses the influence and importance of balance in the use of digital technology in the world of education. Technology not only provides benefits for teachers and students, but also poses several problems and negative impacts. These include misuse of information access, student dependence on technology, reduced social interaction, and character-based education.